Thermal Performance and Energy Efficiency of Different Types of Walls for Residential Building - Awang, Hanizam; Tan, Ying Yi; Mohd Isa, Mohd Hafizal (International Journal of Sustainable Construction Engineering and Technology, 2022)
Decrement factor and time lag play an essential role in determining the thermal performance of a building envelope. Building walls, which form a major part of a building, have great influences on the energy consumption and indoor environment of a room. The indoor temperature considerably increases as the outdoor temperature increases. This scenario leads to excessive reliance on the mechanical cooling system, thereby increasing energy consumption. Therefore, this study aims to investigate the thermal performance and energy efficiency of different wall types. A building with a built-up area of 387.85m2 with six different wall materials is modelled and inputted in Energy Plus simulation software as an Intermediate Data Format file. The maximum and minimum surface indoor and outdoor temperatures are then obtained to determine the thermal performance of the wall material in terms of time lag and decrement factor. The energy efficiency of the wall materials is investigated by obtaining the annual cooling energy of the building made up of different wall materials. Results show that with the time lag of 1 hour, decrement factor of 0.86, annual cooling energy load of 9.52 GJ and cost consumption of RM 608.12, aerated lightweight concrete wall is the most suitable material amongst the six wall materials